THEORETICAL AND PRACTICAL BASIS OF FORMING PERFORMING SKILLS ON FOLK INSTRUMENTS - Shokirkhonov Bakhtiyorkhon Botirkhonovich (Bright Mind Publishing, 2026)
This article covers the historical formation of folk instruments, the pedagogical foundations of developing performing skills, the technology of tuning musical instruments, teaching based on the notation system, performing with piano accompaniment, and organizing stage performance and independent training. The study provides methodological recommendations aimed at improving the technical, musical and psychological preparation of instrumentalists.
Keywords: Folk instruments, performing skills, gijjak, notation system, piano accompaniment, stage performance, independent training